EXPLORING MODERN TECHNIQUES FOR SOLUBILITY ENHANCEMENT IN DRUG FORMULATIONS - BAGADE, PRIYANKA V.; KULKARNI, NILESH S.; CHAUDHARI, PRAVIN D.; DHOLE, SHASHIKANT N.; DESAI, UJWALA S. (International Journal of Current Pharmaceutical Research, 2025)
By addressing the critical gaps in current practices, the objective of the review is to highlight emerging trends and provides insights into the optimization of drug solubility for improved pharmacological outcomes. The literature search was done and rlevent articles were collected from various database like Springer, Science Direct, Taylor and Francis, Wiley and pubmed. Poor solubility of active pharmaceutical ingredients (APIs) significantly hinders their bioavailability and therapeutic efficacy, presenting a critical challenge in drug formulation. This review provides a comprehensive exploration of traditional and advanced techniques for solubility enhancement. Established methods, including salt formation, particle size reduction, and pH adjustment, are compared with cutting-edge strategies such as nanotechnology, electrospun nanofibers, spray drying, and supercritical fluid technology. These innovative approaches leverage mechanisms like particle size reduction, amorphization, and nanostructure engineering to enhance dissolution rates, stability, and controlled release profiles. The article discusses the Biopharmaceutical Classification System (BCS) and its relevance in tailoring solubility enhancement strategies for poorly water-soluble compounds.